ACCOUNTING OF THE SYSTEM OF ECONOMIC SECURITY MANAGEMENT OF THE ENTERPRISE - Nadiia Melnyk (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu, 2017)
The article reveals the importance of accounting for the system of economic security management of the enterprise, regardless of the functions performed by the accountant (informational or informational-analytical). The purpose and the main value of the accounting data (financial) for the management separately for each of the functional components of the company's economic security: internal production (financial, political, legal, intellectual, human resources, technical, technological, informational, environmental, social, power, innovation) and non-productive ( market, interface) are defined. Key words: accounting support, management system, economic security of enterprise, components of economic security of enterprise.